Review paperAlterations of Wnt/β-catenin signaling pathway in hepatocellular carcinomas associated with hepatitis C virus - Rogacki, Karol; Kasprzak, Aldona; Stępiński, Adrian (Polish Journal of Pathology, 2015)
The Wnt/Fzd/β-catenin signaling pathway plays a significant role in physiology and pathology of the liver. The role of β-catenin is linked mainly to the canonical pathway of the system. Phosphorylation of β-catenin and abnormalities in function of the E-cadherin-catenin unit lead to loss of intercellular junctions, progression in liver fibrosis, and development of cirrhosis and hepatocellular carcinoma (HCC). Progression of liver diseases is noted to be accompanied by disturbances in β-catenin expression (mainly with its overexpression), with its cytoplasmic or nuclear translocation and with lowered expression of E-cadherin. Increase in transcriptional activity of β-catenin is associated mainly with mutations of CTNNB1. Detailed mechanisms of HCC development are not known. More β-catenin mutations are manifested in hepatitis C virus (HCV)-associated than in HBV-related HCC. In recent years the role of nonstructural proteins and of the core protein of HCV has been accentuated in induction of the Wnt pathway. HCV proteins affect in a double manner expression of E-cadherin, including modulation of the Wnt pathway and reduction of E-cadherin expression at the transcriptional level. This review presents current data on mechanisms of hepatocarcinogenesis involving participation of the Wnt canonical pathway and, in particular, interaction of Wnt pathway components with HCV genome products in the process.